2000
DOI: 10.1002/(sici)1099-0690(200001)2000:2<313::aid-ejoc313>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

UV Photoelectron Spectroscopy Studies of the Products of Thermal Extrusion of Sulfur Dioxide from Benzosultams

Abstract: An aza‐ortho‐xylylene system is produced by thermal degradation of N‐alkylbenzosultam, which can be directly studied by coupling the system to a UV/photoelectron spectrometer. These thermodynamically unstable xylylene derivatives rearrange to give aldimine by a [1,5] hydrogen shift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…[20] No benzoazetine was detected by UV-PES among the products formed during the thermolysis of 2,1-benzisothiazoline 2,2-dioxide. [21] Scheme 4…”
Section: Discussion Benzoazetines ؊ Aza-ortho-xylylenes Valence Isomesupporting
confidence: 58%
See 2 more Smart Citations
“…[20] No benzoazetine was detected by UV-PES among the products formed during the thermolysis of 2,1-benzisothiazoline 2,2-dioxide. [21] Scheme 4…”
Section: Discussion Benzoazetines ؊ Aza-ortho-xylylenes Valence Isomesupporting
confidence: 58%
“…[18] A thorough comparison of the results of calculations, semiempirical and ab initio, obtained at various theory levels has been performed by Sander et al [18,19] Results of our ab initio calculations at the MP2 theory level suggest a higher stability for aza-ortho-xylylene (9) than for benzoazetine (5). [21] These calculations also confirm a strong tendency towards [1,5]-hydrogen shifts in N-methyl-aza-ortho-xylylene. [21] According to results of semiempirical AM1 calculations, the 6π electrocyclization of N-acyl-aza-ortho-xylylene to N-acyl-3,1-benzoxazine is more favorable than the 4π electrocyclization to N-acylbenzoazetine (Scheme 36, vide infra).…”
Section: Discussion Benzoazetines ؊ Aza-ortho-xylylenes Valence Isomesupporting
confidence: 56%
See 1 more Smart Citation
“…A number of papers have dealt with their use as reactive dienes in preparative organic chemistry. [2Ϫ7] Other work has been devoted to stabilizing these highly reactive species by complexation to transition metals, [8Ϫ11] and to elucidating their properties and reactivity by using time-resolved techniques, [12Ϫ14] photoelectron spectroscopy, [15,16] or matrix isolation spectroscopy. [17Ϫ19] Quinone methides have received attention for their role in the metabolism of a number of preservatives, [20] for their potential use as anti-cancer agents and as active component of insecticides, [21,22] and for their ability to alkylate DNA efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown [22] that sulfur dioxide is eliminated during the photolysis of 1-methyl-2,1-benzothiazoline 2,2-dioxide (benzosultam 16), and N-methylbenzazetine (18) The work in [23] was concerned with investigation of the products from flash-vacuum thermolysis of various substituted benzosultams by UV photoelectron spectroscopy. It was shown that the formation of some products of this reaction (aldimines) is possible as a result both of migration of a hydrogen atom in the initially formed aza-ortho-xylylenes and of the participation of the corresponding benzazetines.…”
Section: Synthesis Of Benzazetines From Sultamsmentioning
confidence: 99%